A comparison of smoking behaviour characteristics between Caucasian smokers in the United Kingdom and Malay smokers in Malaysia - Robson, N.Z. (Elsevier, 2013)
Objectives. There is evidence that smoking behaviour differs by ethnicity. This study aims to compare smoking behaviour characteristics between Caucasian and Malay smokers. Methods. A cross sectional survey, involving 175 smokers attending smoking cessation clinics at the Institute of Psychiatry, London, United Kingdom and University Malaya, Kuala Lumpur, Malaysia between May 2005 and February 2007. Data on demographics, smoking history, nicotine dependence and smoking behaviour were collected. Results. All participants were males, mean age 30.7 ± 10.3 years. Caucasians initiated smoking significantly ear- lier (mean age 14.8 ± 2.8 years) (p = 0.001) and smoked regularly significantly earlier (mean age 17.3 ± 3.5) (p = 0.003) than Malays (mean starting age 16.9 ± 4.4 years and mean age regular use 19.5 ± 4.5 years), re- spectively. Caucasians smoked less for social integration than Malays (p = 0.03) but smoked more for regulation of negative affect than Malays (p = 0.008) and smoked more for hedonism than Malays (p b 0.001). Conclusion. Malays smoke as a means of socially integrating. This has important public health implications. Social reasons and the social environment play a role in smoking uptake, smoking maintenance and smoking cessation and this should be borne in mind for strategies planning to promote smoking cessation.